Frequency And Severity Of Undiagnosed Peripheral Arterial Disease Using Ankle Brachial Index In Diabetic Patients Undergoing Coronary Angiography (Journal of Pharmaceutical Negative Results, 2021)
Background: PAD is characterized by stenosis of non-coronary arteries such the aorta, its visceral branches, and extremity arteries. This is multifocal atherosclerosis. PAD increases the risk of myocardial infarction, stroke, and mortality as well as intermittent claudication and critical limb ischemia. Research shows that people with both coronary artery disease (CAD) and PAD have a greater risk of unfavorable outcomes than those with CAD alone.OBJECTIVE: To determine the frequency and severity of undiagnosed peripheral arterial disease using ankle brachial index in patients undergoing coronary angiography.Study design: A cross sectional study.Place and duration of study. Department of Cardiology Lady Readings Hospital did the six-month study from 05-jan 2020 to 05-july 2020MATERIALS AND METHODS: Department of Cardiology Lady Readings Hospital did the six-month study. The study was descriptive and cross-sectional. PAD prevalence in CAD patients having coronary angiography was 69. WHO formula determined sample size. Continuous non-probability sampling was employed to collect samples with 95% confidence, p= 12.86, and 5% absolute precision.RESULTS: Our study included 69 diabetics with a mean age of 53 years + 8.761. CONLCUSION: Our study concludes that the incidence of PAD (using ankle brachial index) was found to be 15% in which 65% patients had mild PAD (ABI score (0.9-0.75), 25% patients had moderate PAD (ABI score (0.74 to 0.41), 10% patients had severe PAD (ABI score (<0.40).